The The E-Learning Module Arrangement Budgeting Based on Activity-Based Budgeting Model (Case Study: The IT Enterprise in Jakarta) - Santiasih, Wayan; ., Nengzih (International Journal of Scientific Research and Management (IJSRM), 2018)
Budget is one of the management decision-making tools, from activities to finance. One of the budgeting model can be applied is an Activity-Based Budgeting (ABB) model. The objective of this research is to propose the application of the ABB model in IT Enterprise in Jakarta. The object in this research is budgeting for e-learning projects that carried out by IT Enterprise in Jakarta. In the present time, the budgeting model applied is included in the traditional budgeting system, namely the Incremental budgeting model, in which the budgeting is conducted based on the budget in the previous year therefore sometimes the information used is less accurate. This research shows the differences between the ABB model and the Incremental budgeting model, as well as the evaluation of the application of each model. This research is a qualitative research, with descriptive exploratory research type in a case study. Research data was obtained from face to face interviews, observation of activities and documentation. ABB modeling is carried out by detailing activities in e-learning projects including human resources used, then compiling employee costs for these activities. The results of ABB modeling show that ABB has capabilities to provide more accurate information about activities, costs for activities, work process time, amount of human resources needed, total employee costs and project profit / loss. It can be concluded that the ABB model can provides the budgeting model needs of IT Enterprise.